Homicide Phenomena Reflected In Patrick Suskind's Perfume: TheStory Of A Murderer Novel (1985): A Sociological Perspective - Jamilah, Siti Khusnul; , Dr. M. Thoyibi, M.S (2017)
The research discusses about homicide phenomena in Patrick Suskind's novel entitled Perfume: the Story of a Murderer (1985) by using sociological perspective. The objective of the study is to identify homicide phenomena base in the motives and manners of homicide. The researcher uses qualitative research to identify homicide phenomena which were occurred in Germany at around 1980-1985. Primary data of this study is novel entitled Perfume: the story of a Murderer written by Patrick Suskind. Whereas, secondary data of the study is took from some of sources, such as internet, dictionary, and some of books which support the research. The technique collecting data as following: reading the novel Perfume: the Story of a Murderer in English version, reading some of book that relate to the issue and its approach, looking for information from the internet taking note the important things from the primary data and secondary data, the last is classifying of the determine data that relevant to the data. The result of the study shows the meaning of the homicide motive of homicide, and manner of homicide. The other result of the study that related to the sociological of the author as a manifest to write the novel base on the social life in a place where the author was born; that is Germany. It can conclude that homicide phenomena can be done in some of motives and manners.